2016
DOI: 10.1016/j.neuropsychologia.2015.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of episodic memory in semantic dementia: The importance of regions beyond the medial temporal lobes

Abstract: Episodic memory impairment represents one of the hallmark clinical features of patients withAlzheimer's disease (AD) attributable to the degeneration of medial temporal and parietal regions of the brain. In contrast, a somewhat paradoxical profile of relatively intact episodic memory, particularly for non-verbal material, is observed in SD, despite marked atrophy of the hippocampus. This retrospective study investigated the neural substrates of episodic memory retrieval in 20 patients with a diagnosis of SD an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 64 publications
0
38
1
Order By: Relevance
“…To account for this apparent paradox, it has been proposed that the two neurodegenerative disorders may disrupt distinct brain networks related to the MTL [La Joie et al, ; Ranganath and Ritchey, ]. This is in line with the idea that cumulative insult in episodic memory‐related regions beyond the MTL (e.g., medial and lateral parietal cortex) might account for the different episodic memory profiles in AD versus SD [Irish et al, ; Nestor et al, ; Pleizier et al, ]. In support of the network degeneration hypothesis, a recent study showed that cortical regions more impaired in AD versus SD, or reversely, were all connected to the hippocampus in healthy controls [La Joie et al, ].…”
Section: Introductionmentioning
confidence: 88%
“…To account for this apparent paradox, it has been proposed that the two neurodegenerative disorders may disrupt distinct brain networks related to the MTL [La Joie et al, ; Ranganath and Ritchey, ]. This is in line with the idea that cumulative insult in episodic memory‐related regions beyond the MTL (e.g., medial and lateral parietal cortex) might account for the different episodic memory profiles in AD versus SD [Irish et al, ; Nestor et al, ; Pleizier et al, ]. In support of the network degeneration hypothesis, a recent study showed that cortical regions more impaired in AD versus SD, or reversely, were all connected to the hippocampus in healthy controls [La Joie et al, ].…”
Section: Introductionmentioning
confidence: 88%
“…Patients with semantic dementia is characterized by a loss of conceptual knowledge, and this loss may reflect the disruption of a central semantic hub or the degeneration of a temporosylvian language network for verbal concepts (Irish et al, 2014). These patients manifesting in striking alterations in naming and comprehension (Irish et al, 2016). These patients are “characterized by a clear dissociation between marked single-word comprehension” (Agosta et al, 2010), unable to retrieve the names of objects, irregular word reading deficits, identify the color the correct objects, and sparing of fluency, phonology, syntax and working memory (Binder and Desai, 2011).…”
Section: Long-term Memorymentioning
confidence: 99%
“…In contrast, recent studies have confirmed that episodic memory is relatively preserved in SD, particularly when tasks with minimal conceptual loading are employed [12, 13]. The intact performance on traditional non-conceptually loaded episodic memory tasks converges with the performance of SD patients on autobiographical memory tasks.…”
Section: Clinical Presentation and Cognitive Profilementioning
confidence: 99%
“…Taken together, these findings suggest that spared syntactic processing in SD depends on preserved functionality of left frontal, parietal and, to lesser degree, posterior temporal regions. The relative integrity of regions beyond the medial temporal cortices, such as the posterior cingulate and frontal cortices, also seems to sub-serve other cognitive functions such as the preserved episodic memory performance in SD patients [13, 55]. …”
Section: Imagingmentioning
confidence: 99%